You're next - Schachte, Kylie
Flora Calhoun has a reputation for sticking her nose where it doesn't belong. When she gets a midnight call from her terrified ex-girlfriend Ava, she doesn't hesitate...and arrives just in time to see Ava bleed out in a dark alleyway. Determined to do something, Flora sets out on a path of rage and vengeance for all the dead girls whose killers were never found. Her tunnel-vision sleuthing leads to valuable clues about a shocking conspiracy involving her school and beyond, but also earns her sinister threats from the murderer. She has a choice: give up the hunt for answers, or keep digging and risk her loved ones' lives. Either way, Flora will regret the consequences. Who's next on the killer's list?